Recursive Model: Cognitive Learning Behavior in Online Consumers - Christanto Edy, Irwan; -, Riyanto (International Journal of Engineering and Technology, 2019)
Online purchasing decisions are online consumer behavior and are an interesting phenomenon in research. This study aims to prove the concept that online consumer purchasing decisions are influenced by cognitive learning behavior. The main theory underlying this research is consumer behavior and learning. Learning theory is used to analyze consumer learning behavior online with a mix of (crossing) learning theories of behavior and cognitive learning theory. Combination (crossing) between behavioral learning theory, cognitive is called cognitive learning behavior (cognitive learning behavior). This research is a survey. The data used are primary data, with the research instrument in the form of a questionnaire. The subjects of this study are individuals namely online consumers. Online consumers in this study are millennial generation who have made online purchases on one of the e-commerce sites in Indonesia (Matahari.mall, bukalapak, tokopedia, shopee, Zilingo) with this type of product is fashion. In this study 200 respondents were selected. The study consisted of organic stimulation of marketing on the website, online purchasing decisions, cognitive learning, experience preferences. Convenience sampling sampling technique is a sampling method where sampling is based on the availability of elements and the ease of obtaining them. Collecting data with online questionnaires and distributing questionnaires through whatsapp to respondents who are easily contacted by researchers. Data analysis methods with 1) test data quality instruments (validity and reliability), 2) Analysis of Descriptive Statistics and 3) Model Analysis with SEM. The results showed that 1) Organic stimulation of marketing on the website had a positive and significant effect on cognitive learning, 2)experience preference had a positive and significant effect on cognitive learning, 3)cognitive learning had a positive and not significant effect on online purchasing decisions, 4) experience preference had a positive and not significant effect on online purchasing decisions, 5) Organic stimulation of marketing on the website had a positive and significant effect on online purchasing decisions. Â Â